Penerapan Pembelajaran Example-Non Example Dengan Media Alat Peraga Untuk Meningkatkan Pemahaman Konsep dan Habits of Mind Siswa - Andi Bagus Prabowo; Sugeng Sutiarso; Yumiati Yumiati (Departement of Mathematics Education, 2023)
This study aims to improve understanding of mathematical concepts on the subject of spatial structure for fifth grade students of SD Negeri 8 Metro Utara Kec. North Metro Metro City of Lampung Province with the application of the Example Non Example learning model using teaching aids. This type of research is experimental research. Participants were fifth grade students at SD Negeri 8 Metro Utara Kec. North Metro, Metro City, Lampung Province, as many as 20 students. The instrument used to collect data in this study was in the form of observation sheets on the implementation of learning mathematics with the application of the Example Non Example learning model, observations of students and teachers, written tests, and documentation. The results of the study showed that efforts to improve the conceptual understanding of fifth grade students at SD Negeri 8 Metro Utara Kec. North Metro, Metro City, Lampung Province, which is proven to have increased. Increased understanding of students' concepts where in the control class with an average N-Gain score of 279.786%, minimum completeness of 6.25% and maximum completeness of 52.27%. and experienced an increase in the experimental class with an average N-Gain score of 420.113, a minimum completeness percentage of 13.04% and a maximum completeness percentage of 71.43%. This shows that this study achieved the specified completeness indicators, namely completeness, namely completeness above 85%.